Síntese e avaliação da atividade antioxidante de 1,3,4-oxadiazóis e 1,3,4-tiadiazóis contendo os grupos (2-metiltiazolil-4-il), (5-aril-1,3,4-oxadiazol-2- il) e (4-arilseleno)metiltio na posição-5 - Leal, Julliano Guerin (2015)
In the present work, were synthesized thirty three compounds utilizing some cores, with his derivatives present an antioxidant activity previously described, to obtain the final products. The organoselenium, the oxadiazoles, the thiadiazoles and the thiazoles, they were united in differents molecules, with a simple reaction of nucleophilic substitution, with yield of 44-98% to the compounds 1aa-1bc, 52-87% to the compounds 2aa-2da, 64-68% to the compounds 3aa-3ae e 44-84% to the compounds 4aa-4ea. Some compounds be taken to evaluation in vitro of his antioxidant activity, some of this compounds demonstrate this characteristics, but one of them(3aa) have better results front the positive control in radicals elimination assay.